Optimizing the Productivity of the Tandusan Oil Home Industry in Jembrana Through the Implementation of a Digital Platform - Widayanti, Ni Putu Widayanti; Widnyani, Ni Made; Darma, I Gede Wahyu Surya; Gama, Adie Wahyudi Oktavia (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2025)
The Tandusan oil household industry in Baluk-Jembrana Village is a form of local business that produces organic coconut oil. The problem faced by this industrial group is a lack of understanding of product quality and a lack of knowledge in marketing digital-based products. The proposed solution includes education on improving product quality based on predetermined chemical parameters and intensive training in digital platform-based product marketing. The methods used in this activity are Participation Action Research (PAR). This activity's success level is measured through the pretest and posttest. This activity was carried out on September 2, 2023. The number of partner workers who participated in this training activity was 10. With this training, partners' knowledge of product quality increased by eighty-two percent, while partners' knowledge increased by eighty-three percent regarding digital platform-based product marketing.